Solution-based Metal Oxide Semiconductor Memristor - Martins, Raquel Azevedo (2022)
Solution-based memristors have shown a great potential to fulfill several requirements of the Internet of Things (IoT) such as, high density and ultra-low power devices by using low-cost and simple fabrication methods. In this work, solution-processed indium-gallium-zinc oxide (IGZO) thin films are produced using a combustion synthesis process. To improve their performance in memristor devices different parameters are studied: the variation of molar proportion, number of deposited layers and annealing temperature. Memristors with higher number of layers and annealing temperatures show low operating voltage, good endurance, great yield, and retention up to 105 s in air environment conditions. The best condition reached was IGZO (1:3:1) memristor with 7 deposited layers annealed at 300 ºC. These devices can be programmed in a multi-level cell operation mode, up to 8 different resistive states. Furthermore, the same devices show promising features for neuromorphic computing applications since they can emulate the plasticity of a synaptic junction by replicating potentiation and depression. The results achieved are quite promising and even in some cases surpass the current state of the art.